Eight years of PNADC (2012-2019): regularities for quarterly income inequality and labour market - Pitombo Leite, Fabrício (Brazilian Keynesian Review, 2020)
This short note reassess income inequality evolution for Brazil between 2012 and 2019, as represented by the Gini index for the actual household income from all jobs per capita computed from Quarterly Household Survey micro-data. Regularities related to labour market behaviour are drawn, as well as a glimpse of two well-marked periods for the fall and rise of inequality in contemporary Brazil.